A New Nonlinear Equation with Lump-Soliton, Lump-Periodic, and Lump-Periodic-Soliton Solutions. (2nd June 2019) - Ren, Bo; Lin, Ji; Lou, Zhi-Mei
Abstract : An extended (2+1)-dimensional Calogero-Bogoyavlenskii-Schiff-like equation is proposed by using the generalized bilinear operators based on a prime numberp = 3 . By combining multiexponential functions with a quadratic function, the interaction between lumps and multikink soliton is generated. In the meanwhile, the interaction of lump with periodic waves and the interaction among lumps, periodic waves, and multikink soliton can be obtained by introducing the ansätz forms. The dynamics of these interaction solutions are analyzed graphically by selecting appropriate parameters.